2016
DOI: 10.1590/1983-21252016v29n220rc
|View full text |Cite
|
Sign up to set email alerts
|

FUMIGATION TOXICITY OF ESSENTIAL OILS AGAINST Rhyzopertha dominica (F.) IN STORED MAIZE GRAIN

Abstract: -The Rhyzopertha dominica F. (Coleoptera: Bostrichidae) is a primary pest of stored grains in many regions of the world. In this work we evaluated the fumigant activity of essential oils of Ocimum basilicum L., Citrus aurantium L., Mentha spicata L. and Croton pulegiodorus Baill on adult R. dominica in stored maize. Tests were conducted to determine lethals concentrations (CL 50 and CL 100 ) and mortality (fumigation).The fumigation test was done in containers made of glass containing 10 individuals of R. domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
3
12
1
5
Order By: Relevance
“…The proportion of main components obtained in O. basilicum oil, were similar to those described by Kim et al [43] and Souza et al [35]. The genus Ocimum , belonging to the family Lamiaceae, has been investigated with regard to its insecticidal properties against diverse insect pests [35,44,45,46].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The proportion of main components obtained in O. basilicum oil, were similar to those described by Kim et al [43] and Souza et al [35]. The genus Ocimum , belonging to the family Lamiaceae, has been investigated with regard to its insecticidal properties against diverse insect pests [35,44,45,46].…”
Section: Discussionsupporting
confidence: 78%
“…The essential oil of O. basilicum was principally composed by the aromatic ether Estragol (74.0%) and the terpene with alcohol group Linalool (17.8%), which are known to have repellent and toxic activities against stored product insect [42]. The proportion of main components obtained in O. basilicum oil, were similar to those described by Kim et al [43] and Souza et al [35]. The genus Ocimum , belonging to the family Lamiaceae, has been investigated with regard to its insecticidal properties against diverse insect pests [35,44,45,46].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, for example, in kidney beans, Silva et al (2008) found that Croton grewioides Baill essential oil had a fumigant effect on adults of Z. subfasciatus, Brito et al (2015) observed that C. pulegiodorus and Croton heliotropiifolius Kunth essential oils caused 100% mortality in adults of Z. subfasciatus at all concentrations evaluated (5, 10, 15 and 20 µL L -1 air), in addition to having a repellent effect on insects; Carvalho et al (2016) observed toxicity (fumigant effect) of Croton urucurana Baill essential oil on C. maculatus, causing mortality rates greater than 80% and effects on the biology and survival of this beetle. Similarly, in maize, Magalhães et al (2015) reported that C. pulegiodorus and C. heliotropiifolius essential oils had a repellent effect and caused zero emergence of T. castaneum, while Souza et al (2016) observed that C. pulegiodorus essential oil caused mortality rates above 70% in R. dominica, when used at higher concentrations.…”
Section: Resultsmentioning
confidence: 94%
“…The worldwide-distributed genus Croton L. (Euphorbiaceae), in turn, has proven promising for the management of insect pests of stored products (PEREZ-AMADOR et al, 2007). In Brazil, where research on insects that mainly attack beans and cereals has made important progress in recent years, it is worth mentioning the studies analyzing the effect of essential oils from various Croton species on Callosobruchus maculatus Fabricius and Zabrotes subfasciatus Bohemann (Chrysomelidae) (BRITO et al, 2015;CARVALHO et al, 2016), Tribolium castaneum Herbst (Tenebrionidae) (MAGALHÃES et al, 2015), and Rhyzopertha dominica Fabricius (Bostrichidae) (SOUZA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%